Implementation of Flipbook-Based Learning in Elementary Schools - Muna, Raudhatul; Sari, Siti Mayang; Rahmatullah, Rahmatullah (Journal of Educational Sciences, 2025)
This study aims to improve flipbook-based learning outcomes. Technological advancements have shifted educational approaches from traditional methods to more interactive and digital formats. The methodology used was an experimental study featuring a Nonequivalent Control Group, involving two groups of fifth-grade students at SD Negeri 1 Banda Aceh. The experimental group engaged in flipbook-based learning, while the control group adopted conventional techniques. The results showed that students utilizing flipbooks showed a more significant improvement in learning outcomes compared to students in the control group. The experimental group achieved an average posttest score of 85%, reflecting a 50% increase from the pretest, while the control group only saw a 22% increase from pretest to posttest. Furthermore, the integration of flipbooks increased student engagement, made learning more engaging, and facilitated the understanding of abstract concepts. This study recommends that elementary school educators use flipbooks as a digital learning resource and receive adequate training in its implementation. Therefore, flipbook-based learning provides a viable alternative to improve academic achievement and foster student interest in elementary schools.